Risk assessment of calcium carbide use in fruit ripening among farmers, farm workers and fruit traders in the Northern Region of Malaysia - Ismail, Noor Shaeda (2019)
Introduction: Ripening agent is a material that is used to accelerate the fruit ripening activity and calcium carbide (CaC2), a chemical ripening agent, is widely used since antiquity for seasonal fruits ripening purposes. Artificial fruits ripening become dubious in recent years when various health related issues began to arise. Therefore, workplace risk assessment related to CaC2 use is crucial to protect the safety and health of workers from the hazardous impurities. Objective: The general objective of this study is to analyze the potential risks of CaC2 to occupational safety and health (CHRA). Method: This study was performed through the delegation of questionnaires and face to face survey. Pulmonary test and phosphine exposure measurement was also carried out. There were two groups involved in this study which were the exposed groups (172 respondents) and non-exposed group (172 respondents). The study location was conducted in mango farms and fruits stall that used CaC2 as a ripening agent in Perak, Kedah and Perlis. Results: The response rate for exposed respondents was 100% (n = 172). For HIRARC, there were 4 hazard categorized as high risk and medium risk and 1 hazard categorized as low risk while for CHRA analysis, the risk was found significant for those who work directly (work unit A and work unit B) and indirectly with CaC2 (work unit C). The most prevalence respiratory symptom reported for exposed respondent was phlegm (37.8%). It was found that the most contributable factor towards exposed respondent’s lung function was education level (OR = 2.545, p=0.026) while the most contributable factors towards exposed respondent’s respiratory symptoms were marital status for wheezing (OR = 3.428, p=0.002) and chest tightness (OR = 4.876, p=0.000), employment duration (OR = 3.011, p=0.004) for shortness of breath and race for cough (OR = 3.416, p=0.03) and phlegm (OR = 3.241, p=0.024). Conclusions: It is essential to determine the CaC2 exposure towards farmers and fruits trader in order to improve the existing handling of CaC2 and to recover the current method towards a safer approach in order to enhance farmer’s quality of life.